The Diversity of Stingless Bees (Hymenoptera: Meliponini) in Belaban Resort, Bukit Baka Bukit Raya National Park - Patrisia Lindawati; Firman Saputra; Kustiati; Didin Joharrudin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Kelulut (Hymenoptera: Meliponini) is a honey-producing bee and belongs to the eusocial bee group. Kelulut is also a pollinating insect that is widespread in the world, including Indonesia. The study of kelulut diversity can describe the composition of kelulut in an area and the condition of an ecosystem. This study aimed to obtain data and information on kelulut diversity in three different forest areas (primary forest, secondary forest, and ecosystem restoration area). The study was conducted by capturing kelulut using sugar solution bait traps and free sampling. The results obtained were analyzed using the Shannon-Wiener Diversity Index (H'), the Evenness index (E) and the Simpson Dominance Index (C). A total of 747 individuals from 12 types of kelulut were found in this study. The secondary forest gets the highest H' value (1.869), followed by the primary forest (1.672) and ecosystem restoration area (1.159). The diversity of stingless bees is higher in forested areas due to environmental factors such as temperatures within the normal range (25.5-28.9°C), the availability of trees for nesting, and the abundance of food sources from flowers.